Use of pre-operative Midazolam as oral sedation for anxiety reduction amongst patients scheduled for dental extractions under local anaesthesia - Humayun Kaleem Siddiqui,; Khan, Farhan Raza; Wajiha Anzar,; Noureen Batool,; Chapra, Maryam; Jawad Safdar, (Journal of the Pakistan Medical Association, 2026)
Anxiety is a common observation that warrants attention especially for patients scheduled for surgical tooth extraction. A quasi-experimental study was carried out that included sixty (60) patients, booked for surgical extraction at Baqai Dental College, Karachi, Pakistan. Baseline respiratory rate (RR), and blood pressure (BP) were recorded before the administration of the 7.5mg Midazolam (test group). The subjects waited for one hour before the commencement of the dental extraction. The BP and RR were checked again, and the level of anxiety was registered on the modified dental anxiety scale. A significant reduction in the systolic BP, diastolic BP, and RR were observed amongst the participants who were administered pre-procedure Midazolam (p-value <0.001). However, compared to controls, only diastolic BP (p=0.003) and RR (<0.001) reduced significantly in the test group with no notable change in the systolic BP (p-value=0.119). Key Words: Midazolam; Anxiety; Dental extraction; Sedation.